The enrichment ratio of atomic contacts in crystals, an indicator derived from the Hirshfeld surface analysis - Jelsch, Christian; Ejsmont, Krzysztof; Huder, Loïc (IUCrJ, 2014)
The partitioning of space with Hirshfeld surfaces enables the analysis of fingerprint molecular interactions in crystalline environments. This study uses the decomposition of the crystal contact surface between pairs of interacting chemical species to derive an enrichment ratio. This quantity enables the analysis of the propensity of chemical species to form intermolecular interactions with themselves and other species. The enrichment ratio is obtained by comparing the actual contacts in the crystal with those computed as if all types of contacts had the same probability to form. The enrichments and contact tendencies were analyzed in several families of compounds, based on chemical composition and aromatic character. As expected, the polar contacts of the type H...N, H...O and H...S, which are generally hydrogen bonds, show enrichment values larger than unity. O...O and N...N contacts are impoverished while H...H interactions display enrichment ratios which are generally close to unity or slightly lower. In aromatic compounds, C...C contacts can display large enrichment ratios due to extensive π...π stacking in the crystal packings of heterocyclic compounds. C...C contacts are, however, less enriched in pure (C,H) hydrocarbons as π...π stacking is not so favourable from the electrostatic point of view compared with heterocycles. C...H contacts are favoured in (C,H) aromatics, but these interactions occur less in compounds containing O, N or S as some H atoms are then involved in hydrogen bonds. The study also highlights the fact that hydrogen is a prefered interaction partner for fluorine.